A potential tolerogenic immune mechanism in a trophoblast cell line through the activation of chemokine-induced T cell death and regulatory T cell modulation - Fraccaroli, Laura Virginia (2008)
BACKGROUND: Successful implantation is followed by a local pro-inflammatory and Th1 response, subsequently controlled by Th2. Regulated upon activation, normal T cell expressed and secreted (RANTES) promotes a Th1 response and is implicated as a physiologic tolerogenic factor; therefore, we studied its potential role in the trophoblast-maternal leukocyte dialog. METHODS: We performed co-cultures of immortalized trophoblast cell line (Swan 71) and peripheral blood mononuclear cells (PBMCs) from fertile women (n = 23) or with recurrent spontaneous abortions (n = 18, RSA). After 24 and 48 h, supernatant and cells were analyzed by enzyme-linked immunosorbent assay, fluorescence-activated cell sorting, Western blot and apoptosis assay. To investigate the physiological effects at peripheral level, we co-cultured maternal and paternal PBMCs with conditioned media from Swan cells and progesterone. RESULTS: Following interaction of maternal PBMCs and trophoblast cells, RANTES production increased (P < 0.05) and was accompanied by low levels of interferon gamma, interleukin-12 p70 and high levels of tumor necrosis factor-alpha, nitrites and leukemia-inhibitory factor. RANTES production resulted in elevated apoptosis of potentially deleterious maternal CD3+ lymphocytes, accompanied by a decrease in the proliferative maternal response. During fetal-maternal dialog, the anti-RANTES antibody significantly reduced the frequency of CD4+CD25+Foxp3+ cells (P < 0.05) and was associated with trophoblast cell survival. However, co-cultures of Swan cells and RSA-PBMCs displayed a differential RANTES kinetics, lower levels of regulatory T cells (Tregs) and CD3+annexin-V+cells, accompanied by higher levels of apoptotic trophoblast cells. CONCLUSIONS: RANTES promotes an adequate pro-implantatory microenvironment that influences trophoblast cell survival and modulates the balance of maternal Treg/T effector lymphocytes in favor of maternal tolerance.